Temperature And Humidity Control Based On Quail Eggs - Dian Efytra Yuliana (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2020)
In quail DOQ cultivation after the quail eggs hatch, DOQ (Day Old Quail) quail chicks need a warm place as a substitute for the mother to maintain the temperature of the body, because in this phase quail chicks have not been able to adjust to room temperature. If the temperature is not suitable, it will cause quail death. From these problems, a quail DOQ cage control system was made using microcontroller. This system consist of a DHT11 sensor as a detector of temperature and humidity, and Arduino as a controller of the system. The heat source in the DOQ room uses a DC bulb equipped with a blower to spread the heat, the signal from the sensor is used as a parameter controlling the temperature and humidity of the cage by adjusting pwm on Arduino when the temperature in the cage is too hot or less hot and the humidity is less humid. To display the temperature of the border space, a 16x2 LCD display is used. From the fuzzy logic test results obtained an error percentage of 1% humidity of 2% and a mortality rate of 0% and without using fuzzy logic a mortality rate of 20%.DOI : https://doi.org/10.26905/jeemecs.v3i2.4354